일반답과 간척답에서 사료용벼 재배시 생육특성 및 사료가치 - 조광민; Kwang-min Cho; 백남현; Nam-hyun Back; 양창휴; Chang-hyu Yang; 신평; Pyung Shin; 노태환; Tae-hwan Noh; 이건휘; Geon-hwi Lee; et al. (Korean journal of crop science, 2014)
This study was carried out to compare the growth characteristics and feed values of the whole crop silage rice from paddy field and reclaimed paddy field. The heading dates of tested varieties was August 8 to August 30 in the paddy field, 1~2 days later than the reclaimed paddy field's August 6 to August 29. Plant height was in the range of 105~135 cm in paddy field, and 97~126 cm in reclaimed paddy field, respectively. The plant height of Mokyang was tallest in the paddy field, but Suwon 544 was tallest in the reclaimed paddy field. The number of tiller per plant of Nokyang was largest in the paddy field. Dry matter (DM) yield of whole crop rice ranged from 15.26 to 23.24MT ha -1 in the paddy field and 11.94 to 18.89 MT ha -1 in the reclaimed paddy field. The highest DM yield in both fields was attained by Mokwoo. Comparing with the paddy field, the reclaimed paddy field achieved 78~84% in the DM yield. The crude protein content of varieties was 8.5 to 11.6% in the reclaimed tidal land and 6.7~8.7% in the paddy field. Neutral detergent fiber (NDF) of varieties in both fields ranged from 31.2 to 55.5%. Suwon 544 recorded the highest NDF contents in both fields. All varieties did not show any significant difference in acidic detergent fiber (ADF) which had values ranging from 22.3 to 33.2%. Total digestion nutrient (TDN) was more than 60% overall in both fields. Regarding TDN yield, Mokwoo recorded 16.54 MT ha -1 in reclaimed tidal land and 12.69 MT ha -1 in the paddy field, which showed the highest figure among the varieties. These results suggest the feasibility for cultivation of the whole crop silage rice in reclaimed paddy field, which showed 80% of the yield compared to paddy field, and implied that Mokwoo would show the most excellent yield and feed value.